Enhancing shopping mall spatial configuration and design a study on shopping malls in Tagum City through syntactic analysis and wayfinding - Judan, Mavelle Marcilyne V. (2021)
Impacts and relationship between space configuration, users? satisfaction and spatial cognition can be constructed through spatial design. Strategic marketing and planning approach should not only explore space economics but should also optimize space layout and configuration based on consumers and visitor?s movement, wayfinding, and satisfaction of the space which builds popularity and attractiveness of shopping centers and provides higher revenue through the increase number of visitors. Studying user mall traffic and users? spatial cognition and spatial layout could add insights in improving shopping mall design. Thus, this paper attempted to study the relationship between the spatial configuration and user traffic and its effects to user?s wayfinding and satisfaction. In conclusion, the researcher was able to determine that syntactic measures affect the volume of traffic inside the shopping mall. Movement was also observed to identify possible spatial layout and design. However, the study has also determined that there are also other factors that affects costumer's visit and patronage in the shopping mall. The researcher has taken the following details into consideration and used them in creating design guidelines for the proposed project.